Conflict Management Practices In Tertiary Institutions: The Case Of University For Development Studies Central Administration, Ghana - Mohammed, Bawah; Adam Andani, Mohammed; Md Sayed, Uddin (IJDR, 2019)
The purpose of this paper is to evaluate conflict management practices and the main causes of conflict in the university administration in Ghana. The researcher used quantitative methods to classify variables in the study and administered questionnaires as tools to enable accurate data collection. The target population for the research included management staff, senior staff and junior staff at the University for Development Studies UDS central administration in Tamale, Ghana. The study revealed that the causes of conflict at the UDS central administration were conflicting needs, conflicting perception, conflicting goals, conflicting roles, tribalism and nepotism. The strengths and weaknesses of the processes and procedures in conflict management and resolution were discovered with the view to recommend ways of improvement. The findings may draw the attention of policy makers and other stakeholders to various issues in the conflict management and resolution processes in public universities on how to address problematic issues. The study may also highlight the processes and quality procedures for conflict resolution in the tertiary institutions. The paper’s originality is reflected by the use of management staff, senior staff and junior staff which have not been previously used, to investigate university conflict management in the study area.